Developing a Standard Tool for Measuring Health Literacy Related to Transfusion-Transmitted Infections - Leila Manzouri MD; Saman Masoudifar PhD; Narges Roustaei PhD; Fariba Rad PhD (Plasmatology)
Background Transfusion-transmitted infections (TTI) are among the most critical challenges of blood transfusion. Patients with lower health literacy can have adverse consequences for blood transfusion and due to the lack of standard tools for measuring health literacy related to TTI, this study was conducted to develop a standardized tool for assessing Health literacy associated with TTI. Aim This study aimed to develop a standardized tool for assessing Health literacy related to TTI. Material and Methods This study was a cross-sectional analytical study of the tool development and validation type, according to the definitions provided for health literacy, questions were designed in the five areas of search, understanding, evaluation, decision-making, and application. The questionnaire was provided to relevant experts to evaluate the content validity with a qualitative and quantitative approach. After making corrections according to the experts’ opinions, the Content Validity Index (CVI) and the Content Validity Ratio (CVR) were checked. It was given to people who were at least literate in reading and writing levels to check the quantitative and qualitative face validity. Finally, the structural validity of the tool was checked by performing a confirmatory factor analysis and its reliability by calculating Cronbach's Alpha. Results The CVR and CVI had an average of 0.86 and 0.93 respectively. The reliability of the questionnaire was calculated using Cronbach's alpha coefficient of 0.744. In examining the structural validity of the tool, the root mean squared error (RMSE) index was less than 0.0001, the Goodness of Fit Index (GFI) was 0.975, the Adjusted Goodness of Fit Index (AGFI) was 0.957, Bentler and Bonnet's Normed Fit Index (NFI) was 1 and Comparative Fit Index (CFI) was 0.856. Conclusion The tool developed is reliable and valid, and can be used to measure the level of health literacy related to transfusion-transmitted infections.